Pursuing human-relevant gut microbiota-immune interactions - Spencer, Sean P. (Immunity, 2019)
The gut microbiota is a complex network of diverse organisms that exhibits plasticity and is capable of impacting host immunity. The malleability of the microbiota presents microbial alteration as an avenue for tuning the immune system to different set points, an approach that has the potential to enable a wide range of therapeutic applications, and ultimately enable disease prevention. Despite the tremendous potential in harnessing the microbiome-immune axis to benefit human health, key barriers must be addressed to hasten translation. Studies using mouse models have identified numerous specific interactions between the gut microbiota and both local and systemic immunity, in several cases using gnotobiotics and other highly controlled approaches to establish causal relationships. Recent advances in our ability to perform expansive profiling of both the microbiota and the immune system now enable exploring human-gut microbiota connections more thoroughly than ever before. An important next step in realizing the power of microbiome reprogramming is to elucidate a human-relevant “map” of microbial-immune wiring, while focusing on animal studies to probe the subset of interactions likely to be relevant to human biology. Such efforts have the potential for revealing new paradigms in immune function as it relates to the microbiome, and for harnessing this connection to improve human health. Here we provide an overview of this field’s current status and discuss two approaches for establishing priorities for detailed investigation: (i) longitudinal intervention studies in humans probing the dynamics of both the microbiota and the immune system, and (ii) the study of traditional populations to assess lost features of human microbial identity whose absence may be contributing to the rise of immunological disorders. These human centered approaches offer a judicious path forward to capitalize on the potent power of the microbiota as a driver in immune health.